Pengaruh Customer Perceived Value , Service Quality, Dan Physical Environment Terhadap Kepuasan Dan Kesetiaan Pelanggan - Shelly Agustina Natawijaya; Keni (Universitas Tarumanagara, 2018)
The aim of this study are : First, to explore the effect of customer perceived value , service quality, and physical environment on customer loyalty. Second, to explore the effect of customer perceived value , service quality, and physical environment on customer satisfaction. Third, to explore the effect of customer satisfaction towards customer loyalty. Fourth, to find out if customer satisfaction can mediate customer perceived value , service quality, and physical environment towards customer loyalty. The method of data collection is purposive sampling. The samples of this research are collected from 326 respondents, who are the customers of furniture store in Jakarta. The technique of data analysis used in this study was regression analysis and mediating test to find put the hypotheses. The results are : (a) the relationship between customer perceived value , service quality, and physical environment have a significant and positive impact toward customer loyalty; (b) the relationship between customer perceived value , service quality, and physical environment have a significant and positive impact toward customer satisfaction; (c) customer satisfaction has a positive impact on customer loyalty; (d) customer satisfaction will mediate the effect of customer perceived value , service quality, and physical environment towards customer loyalty.